2001
DOI: 10.3109/08977190109001076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-17 onIn VitroHematopoietic Progenitor Cells Growth and Cytokine Release in Normal and Post-irradiated Murine Bone Marrow

Abstract: The influence of recombinant human IL-17 on granulocyte-macrophage (CFU-GM) and erythroid (BFU-E and CFU-E) progenitors and the release of IL-la/fl, IL-6 and erythropoietin (EPO) was estimated in the bone marrow cells obtained from normal and sublethally irradiated mice. In normal mice IL-17 increased CFU-GM and BFU-E and reduced CFU-E derived colonies numbers and augmented release of ILL-6 and EPO. In irradiated mice the effects of IL-17 on hematopoietic progenitors were lineage-dependent, as well as dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…However, the complex interplay between successfully controlling an infection and the generation of inflammatory-derived anemia during a malaria infection is difficult to discern at the molecular level [62]. IL-17 is a prototypical example of such complexity since IL-17 bridges immune and hematopoietic regulation by stimulating early stage erythroid progenitors (i.e., burst forming unit erythroid, BFU-E) [63], and in the opposite context, inhibits late stage erythroid progenitors [30, 64, 65]. Further studies are required to delineate the influence of genetic polymorphisms within IL-23R on differential expression and production of inflammatory mediators to unravel the molecular mechanisms through which the IL-23/T-helper 17 axis collectively influences the development of malarial disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the complex interplay between successfully controlling an infection and the generation of inflammatory-derived anemia during a malaria infection is difficult to discern at the molecular level [62]. IL-17 is a prototypical example of such complexity since IL-17 bridges immune and hematopoietic regulation by stimulating early stage erythroid progenitors (i.e., burst forming unit erythroid, BFU-E) [63], and in the opposite context, inhibits late stage erythroid progenitors [30, 64, 65]. Further studies are required to delineate the influence of genetic polymorphisms within IL-23R on differential expression and production of inflammatory mediators to unravel the molecular mechanisms through which the IL-23/T-helper 17 axis collectively influences the development of malarial disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 is produced by activated T-cells and is involved in priming of T-cells through its ability to stimulate macrophages and some epithelial cells to produce pro-inflammatory mediators [e.g., IL-1, IL-6, TNF-α, NOS-2, metalloproteases known to be important in inflammatory diseases [26, 27]. IL-17 is also important in linking immune responses with erythropoiesis through its ability to enhance proliferation of erythroid precursor cells [2830]. Although IL-17 has not previously been explored during malaria mono-infection in the cohort of children investigated here, we have shown that IL-17 has a significant positive association with Hb in malaria-infected children with HIV-1 [31].…”
Section: Introductionmentioning
confidence: 99%
“…IL-17 signaling regulates G-CSF expression, as well as the expression of other cytokines that increase circulating neutrophil numbers. 25,27,[34][35][36] The effect of IL-17 on neutrophil numbers stems from its ability to increase G-CSF mRNA stability that ultimately leads to a systemic increase in G-CSF concentrations. 23 Mice lacking IL-17 have previously been shown to be more sensitive to TBI than normal mice in that they have a reduced LD 50 from 8.5 Gy in female C57BL/6 mice to 7.25 Gy in female IL17ra Ϫ/Ϫ mice and also experience increased myelotoxicity after radiation confirming an important role of IL-17 in protection from radiation-induced hematologic damage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that oncostatin M and IL-17 produced by T cells can stimulate IL-6 production by endothelial cells and osteocytes (32,36). IL-6 has an important effect on neutrophil production.…”
Section: The First Problem: How T Cells Can Help Hematopoiesismentioning
confidence: 99%
“…Indeed, CD4 + T cells are wonderful cytokine producers, not only quantitatively, but also qualitatively, including the major T cell cytokines that control the immune responses such as IFN-γ, IL-4, IL-5, IL-13, IL-10 and TGF-ß, and the "minor" cytokines, whose effects on adaptive immune responses are less prominent (29). This group includes GM-CSF, IL-3, IL-6, IL-17, and oncostatin M -all involved in the regulation of hematopoiesis (30)(31)(32)(33)(34)(35)(36)(37). The major problem is that most of these cytokines are not T cell exclusive.…”
Section: The First Problem: How T Cells Can Help Hematopoiesismentioning
confidence: 99%